An interactive serious game to Target perspective taking skills among children with ASD: A usability testing. Issue 16 (10th December 2021) - Ghanouni, Parisa; Jarus, Tal; Zwicker, Jill G.; Lucyshyn, Joseph
ABSTRACT: Autism spectrum disorder (ASD) is a childhood disorder which affects social and interpersonal communication. Using video game programmes might be considered as complementary assistive technology tools to teach socio-emotional skills; however, there has been limited incorporation of the view and input of key stakeholders during the design of these programmes. This study aimed to collect stakeholders' ideas by involving 20 participants, including children and youth with high functioning ASD, and their parents, during usability testing of an interactive motion gaming programme that focuses on perspective taking. After developing the game in consultation with stakeholders, we asked participants to provide us with feedback on how to further improve it. Participants commented on three main areas that should be elevated including: (a) design– How it looks and sound, (b) maintaining engagement – How it feels, and (c) fine-tuned feedback. This helped us to incorporate the user's ideas and enhance the user-friendliness of the system prior to launching the system. This study is one of the first projects that incorporated both children/youth with ASD and their parents' comments during the development of a novel motion gaming programme to address perspective taking.